2002
DOI: 10.1046/j.1468-2982.2002.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acetaminophen and Naproxen in the Treatment of Tension-Type Headache. A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: The objective of this study was to evaluate and compare the efficacy and safety of single doses of acetaminophen (paracetamol) 1000 mg and naproxen 375 mg vs. placebo over a six-hour period in the treatment of tension-type headache. The treatments were compared in a randomized, double-blind, multicentre, placebo-controlled study. Efficacy was evaluated using four standard analgesic summary endpoints (the sum of pain intensity differences from baseline, the maximum pain intensity from baseline, the sum of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 15 publications
1
41
0
1
Order By: Relevance
“…[9][10][11][12] Paracetamol has not been shown to be effective at doses below 1,000 mg and some studies have shown it to be less effective than NSAIDs. Combination analgesics containing caffeine may be more effective still, 13 but are likely to carry a greater propensity to induce medication overuse headache -though it is unlikely that patients with TTH alone, without a personal or family history of migraine, are susceptible to this condition.…”
Section: Tension-type Headachementioning
confidence: 99%
“…[9][10][11][12] Paracetamol has not been shown to be effective at doses below 1,000 mg and some studies have shown it to be less effective than NSAIDs. Combination analgesics containing caffeine may be more effective still, 13 but are likely to carry a greater propensity to induce medication overuse headache -though it is unlikely that patients with TTH alone, without a personal or family history of migraine, are susceptible to this condition.…”
Section: Tension-type Headachementioning
confidence: 99%
“…In treatment trials, aspirin doses of 500 to 1,000 mg and acetaminophen doses of 1,000 mg were utilized. In terms of NSAIDs, ibuprofen doses of 200 to 400 mg, naproxen sodium doses of 375 to 550 mg, ketoprofen doses of 25 to 50 mg, and diclofenac potassium doses of 50 to 100 mg all have demonstrated efficacy [8][9][10][11].…”
Section: Abortive Treatmentmentioning
confidence: 99%
“…Simple analgesics Most randomized placebocontrolled trials have demonstrated that aspirin in doses of 500 mg and 1000 mg [Steiner et al 2003] and acetaminophen (paracetamol) 1000 mg [Steiner et al 2003;Prior et al 2002] are effective in the acute therapy of TTH. One study found no difference in efficacy between solid and effervescent aspirin [Langemark and Olesen 1987].…”
Section: Acute Pharmacotherapymentioning
confidence: 99%